Descending aortic transection for recurrence of a pseudoaneurysm previously treated with a stent graft after extra-anatomical bypass for aortic coarctation: a case report - Keisuke Shibagaki; Shingo Kunioka; Yuta Kikuchi; Naohiro Wakabayashi; Tomonori Shirasaka; Natsuya Ishikawa; Hiroyuki Kamiya (Surgical Case Reports)
Abstract Background In adult patients with primary or recurrent coarctation of the aorta (CoA), extra-anatomic bypass grafting (EABG) has been widely used as a surgical treatment option. However, there have been few reports on pseudoaneurysms (PAs) of the distal anastomotic sites after extra-anatomic bypass for CoA. Case presentation A 51-year-old man with hemoptysis was transferred to our hospital. Twenty years ago, he had undergone EABG from the ascending to the descending aorta (ascending-to-descending EABG) for CoA with right aortic arch. Eight years ago, he underwent thoracic endovascular aortic repair (TEVAR) for the ruptured PA on the distal anastomotic site of the EABG. Contrast-enhanced computed tomography scans revealed recurrent ruptured PA on the distal anastomotic site of the EABG. Therefore, we decided to replace the descending aorta, followed by end-to-side anastomosis of the EABG to the replaced descending aorta. However, due to massive adhesion of the lung to the EABG and PA, we performed transection of the descending aorta to decompress the PA. The postoperative course was uneventful, and the patient is doing well 5 months after surgery. Conclusions Aortic transection between the CoA and the distal anastomosis site may be a useful additional procedure in patients previously treated with TEVAR for PAs in the distal anastomosis site after EABG.